HUBUNGAN KEPUASAN PETANI JAGUNG TERHADAP KINERJA PENYULUH PERTANIAN DI DESA MOROME KECAMAAN KONDA KABUPATEN KONAWE SELATAN - Abdul Samad; Sukmawati Abdullah; Tjandra Buana (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
The phenomenon of corn farmer satisfaction is still an important indicator for extension workers. In this case, the performance of extension workers is a point that can determine farmer satisfaction based on the problems faced by farmers so that solutions and innovations by extension workers can be delivered with the main objective of farmers' needs. This research aims to determine the satisfaction of corn farmers and the performance of extension workers in Morome Village, Konda District, South Konawe Regency, and to see the relationship. The population in this study were all corn farmers in Morome Village, Konda District. Considering that the population is only 30 Corn Farmers, it is appropriate to take all of them as samples without having to take a certain number of samples (saturated sample method/census). Data collection techniques in this research were observation, interviews and documentation. The instrument used was a questionnaire. Type of quantitative research. The data analysis used to determine the satisfaction of corn farmers and the performance of agricultural instructors is using the class interval formula, while the data analysis used to determine the relationship between corn farmer satisfaction and the performance of agricultural instructors is using the Spearman rank correlation formula. The results of this research show that general farmer satisfaction in Morome Village is in the high category. This can be seen from the aspects of quality, service and value which are in the high category, then the performance of agricultural instructors in Morome Village is generally in the high category too. This can be seen from the aspects of extension planning, implementation of extension, evaluation and reporting which are in the high category. Farmer satisfaction has a positive and very close relationship with the performance of instructors in agricultural extension activities in Morome Village. Where when farmer satisfaction increases, the performance of extension workers also increases and vice versa.